Value of Chest Radiographic Pattern in RSV Disease of the Newborn: A Multicenter Retrospective Cohort Study - Américo Gonçalves; Gustavo Rocha; Hercília Guimarães; Paula Cristina Fernandes; Elisa Proença; Dulce Oliveira; Paula Rocha; Conceição Quintas; Teresa Martins; Alice Freitas; Clara Paz Dias; Albina Ramires (Critical Care Research and Practice)
Respiratory syncytial virus (RSV) lower respiratory tract infection is the most common viral respiratory infection in infants. Several authors have sought to determine which risk factors are the best predictors for severe RSV disease. Our aim was to evaluate if a specific chest radiographic pattern in RSV disease can predict the disease severity. We conducted a multicenter retrospective cohort study in term and preterm neonates with confirmed lower respiratory tract RSV infection, admitted to neonatal intensive care units (NICU) from 2000 to 2010. To determine which factors independently predicted the outcomes, multivariate logistic regression analysis was performed. A total of 259 term and preterm neonates were enrolled. Patients with a consolidation pattern on the chest radiograph at admission (n=101) had greater need for invasive mechanical ventilation (OR: 2.5; P=.015), respiratory support (OR: 2.3; P=.005), supplemental oxygen (OR: 3.0; P=.008), and prolonged stay in the NICU (>7 days) (OR: 1.8; P=.025). Newborns with a consolidation pattern on admission chest radiograph had a more severe disease course, with greater risk of invasive mechanical ventilation, respiratory support, supplemental oxygen, and prolonged hospitalization.